2020
DOI: 10.1094/pdis-10-19-2198-re
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mapping of Adult Plant Resistance to Leaf Rust and Stripe Rust in CIMMYT Wheat Line Arableu#1

Abstract: Leaf (brown) rust (LR) and stripe (yellow) rust (YR), caused by Puccinia triticina and P. striiformis f. sp. tritici, respectively, significantly reduce wheat production worldwide. Disease-resistant wheat varieties offer farmers one of the most effective ways to manage these diseases. The common wheat (Triticum aestivum L.) Arableu#1, developed by the International Maize and Wheat Improvement Center and released as Deka in Ethiopia, shows susceptibility to both LR and YR at the seedling stage but a high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Due to different responses to FOV4 among different cotton cultivars, the disease progression caused by FOV4 may follow a sigmoid model if some of the cultivars have resistance genes in response to FOV4 infections during early stages of infections at both 7 and 14 days post-inoculations, as shown by Zhang et al ( 2021b ). It is also a well-known fact that many genes or quantitative trait loci (QTLs) confer adult resistance but not at the seedling stage in cereal crops (Chen, 2013 ; Zhou et al, 2019 ; Yuan et al, 2020 ). Our results showed that the increase in mortality for highly susceptible genotypes like the Pima S-7 cultivar (with ca.…”
Section: Discussionmentioning
confidence: 99%
“…Due to different responses to FOV4 among different cotton cultivars, the disease progression caused by FOV4 may follow a sigmoid model if some of the cultivars have resistance genes in response to FOV4 infections during early stages of infections at both 7 and 14 days post-inoculations, as shown by Zhang et al ( 2021b ). It is also a well-known fact that many genes or quantitative trait loci (QTLs) confer adult resistance but not at the seedling stage in cereal crops (Chen, 2013 ; Zhou et al, 2019 ; Yuan et al, 2020 ). Our results showed that the increase in mortality for highly susceptible genotypes like the Pima S-7 cultivar (with ca.…”
Section: Discussionmentioning
confidence: 99%
“…These QTL explained 6−13% of the phenotypic variance. Several studies involving biparental mapping populations and genome‐wide association mapping have identified small‐ to medium‐effect inconsistent QTL in CIMMYT wheat germplasm corresponding to the same chromosomes (Basnet et al., 2014; Gao et al., 2016; Lan et al., 2014; Yuan et al., 2020). It is more likely that these four QTL represent the previously reported leaf rust resistance loci in CIMMYT lines.…”
Section: Discussionmentioning
confidence: 99%
“…Association mapping identified genomic regions for leaf rust resistance on chromosomes 2B, 3A, and 5D. In another study, a QTL was reported on chromosome arm 3DS in the CIMMYT line ‘Arableu#1’, which explained up to 4% phenotypic variance (Yuan et al., 2020). Arableu#1 has one parent line common with Copio in their pedigrees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conclude that QYr.cim-1BL/QLr.cim-1BL should be the known APR gene Lr46/Yr29/Sr58/Pm39. Over the last two decades, many CIMMYT derived bread and durum wheat have been reported to possess Lr46/Yr29/Sr58/Pm39: for example, "Pavon 76" (William et al, 2006), "Saar" (Lillemo et al, 2008), "Pastor" (Rosewarne et al, 2012), "Quaiu 3" (Basnet et al, 2013), "Francolin#1" (Lan et al, 2014), "Sujata" (Lan et al, 2015), "Kundan" (Ren et al, 2017), "Bairds" (Lan et al, 2017b), "Chilero" (Ponce-Molina et al, 2018), and Arableu#1 (Yuan et al, 2020). Based on all reported studies, Lr46/Yr29/Sr58/Pm39 should be placed from 662.1 to 684.8 Mb, according to the CS reference genome (International Wheat Genome Sequencing Consortium, 2018).…”
Section: Resistance Loci On Group Chromosomesmentioning
confidence: 99%